INCONSISTENCY OF MERITOCRACY IN PPPK LECTURER CAREER RIGHTS: ISLAMIC LAW AND HUMAN RIGHTS REVIEW - Tobroni, Faiq; Kamala, Izzatin (UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
This research aims to analyse the policy on the placement of lecturers as Government Employees with Work Agreements (PPPK), which raises serious issues in the higher education system, especially in terms of protecting the career rights of PPPK lecturers. The used method is a normative-empirical approach with a literature study of laws and regulations, policy documents, and Islamic literature. In addition to documents, researchers also used interviews with PPPK lecturers as triangulation in tracing the facts of regulation implementation. This study found that there is an inconsistency in the implementation of the meritocracy principle in treating PPPK lecturers. Although regulations on the State Civil Apparatus (ASN) promise the meritocracy principle, it does not apply to the career protection of PPPK lecturers. They cannot apply for promotion to functional positions (junior assistant professor, senior assistant professor, asssociate professor, and Professor). Some PPPK lecturers placed in the functional position of junior assistant professor at the time of recruitment, they cannot apply for a functional promotion to senior assistant professor. In contrast, all of these functional promotion facilities apply to Permanent Civil Servants (PNS). Like PPPK, PNS is a part of ASN. This inconsistency shows serious problems in terms of human rights and Islamic law. In terms of human rights, the government has failed to carry out its duties as a duty bearer of human rights in protecting the career rights of PPPK lecturers. The inconsistency of meritocracy contradicts the perspective of Islamic law, which emphasises justice, equality, and trust in human resource development. The government has actually become an actor that perpetuates the injustice of treatment in managing ASN.